2013
DOI: 10.1080/21553769.2013.879266
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium rhizogenes-mediated transformation of a multi-medicinal herb,Boerhaavia diffusaL.: optimization of the process and anti-microbial activity against bacterial pathogens causing urinary tract infections

Abstract: Hairy root cultures (HRCs) of Boerhaavia diffusa L., an ethno-medicinally important herb, were established via explant co-cultivation with Agrobacterium rhizogenes. Several key factors influencing transformation efficiency were optimized. Rhizoclones showing prolific growth were maintained through successive subcultures in solidified Murashige & Skoog's medium without growth regulators (MS0) under diffused illumination. PCR analysis of the rhizoclones demonstrated positive amplification of rolB and rolC genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…The presently observed exclusive susceptibility of leaf explants and total failure of stem segments towards A. rhizogenes-mediated hairy root induction contradict the earlier findings of Sahu et al (2013Sahu et al ( , 2014, who have demonstrated notable susceptibility of intermodal segments of in vivo-grown B. diffusa plants towards the peak limit of hairy root induction. The disparity in the maturity levels of the utilized explants could be one of the causes for the observed difference in susceptibility of the nodal segments, as the maturation status of explants predominantly impacts the availability of functionally competent cells (as well as their internal hormonal levels), which essentially serve as ideal targets for hairy root induction (Potrykus 1990).…”
Section: Induction and Establishment Of Hairy Rootscontrasting
confidence: 75%
See 2 more Smart Citations
“…The presently observed exclusive susceptibility of leaf explants and total failure of stem segments towards A. rhizogenes-mediated hairy root induction contradict the earlier findings of Sahu et al (2013Sahu et al ( , 2014, who have demonstrated notable susceptibility of intermodal segments of in vivo-grown B. diffusa plants towards the peak limit of hairy root induction. The disparity in the maturity levels of the utilized explants could be one of the causes for the observed difference in susceptibility of the nodal segments, as the maturation status of explants predominantly impacts the availability of functionally competent cells (as well as their internal hormonal levels), which essentially serve as ideal targets for hairy root induction (Potrykus 1990).…”
Section: Induction and Establishment Of Hairy Rootscontrasting
confidence: 75%
“…Different solvents have been used to screen the antibacterial property of both root and aerial parts of B. diffusa with variable results involving both Gram-negative and Gram-positive bacteria (Murti et al 2010;Ramachandra et al 2012;Malhotra et al 2013;Sahu et al 2013). Enhanced antimicrobial activity of RBH hairy root clone than that of its control roots against S. aureus has corroborated a previous report demonstrating better performance of Maytenus senegalensis hairy roots than the control roots against the same bacterium (Jain et al 2008).…”
Section: Antibacterial Activitysupporting
confidence: 64%
See 1 more Smart Citation
“…The faecal collected from Institute of Medical Sciences & SUM Hospital, Bhubaneswar, Odisha. Cryptococcus neoformans was obtained from the University Department of Pharmaceutical Sciences, Utkal University 22 . Amoxicillin (Reference Antibiotic: RA) and ampicillin (RA 1 ) were used as reference antibacterial antibiotics, and fluconazole (RA) was used as a reference antifungal antibiotic.…”
Section: Methodsmentioning
confidence: 99%
“…One of the targets of mission 2035 by WHO is to make the world TB free by the end of 2035 leaving no patient with persistent TB [19]. Many plant species have always shown potential in ancient history to treat the medical disorder with promising therapeutic agents [20]. The knowledge about single chemical component encompassed by medicinal plant plays a critical role from method of extraction to understanding pharmacological assay and possible toxicity.…”
Section: Introductionmentioning
confidence: 99%